STRUCTURAL CHARACTERIZATION OF AGAR EXTRACTED FROM SIX RED SEAWEED SPECIES GROWING IN THE COAST OF VIETNAM - Tran Thi Thanh Van; Bui Minh Ly; Ngo Quoc Buu; Chu Dinh Kinh (Universitas Gadjah Mada, 2008)
Polysaccharides extracted from six red seaweed species growing in Vietnam have been studied. Characterisation of their structure by chemical and spectroscopic methods showed that all of them have a basic repeating structure of alternating 3-linked b-D-galactopyranosyl and 4-linked 3,6-anhydro a-L-galactopyranosyl units with substituted methyl ether groups. The native agar offers only weak gelling abilities owing to the 4-linked a-L-galactopyranosyl 6-sulfate as its precursor. Conversion of this unit into the corresponding 3,6-anhydride by treating with hot alkali generally led to gel strength increasing. The agars from G. fisheri and G. firma are poorly substituted, while those from G.asiatica, G.tenustipitata and G. heteroclada are partly methylated on position 6 of the 3-linked b-D- galactose. Agar from Gelidiella acerosa is partlly methylated on both positions 6 and 2 of the 4linked 3,6-anhydro a-L-galactose. The alkali- modified agars have been obtained in acceptable quantities with gel strength of 300932 g/cm2. The obtained results showed that all the six algal species are suitable as raw material for commercial agar production and worthy of further cultivation